Capítulo 4 — Restauración de los Árboles Después de Un Huracán - Edward F. Gilman; Traci Partin (EDIS)
ENH-1054-SP, an 11-page full color fact sheet by Edward F. Gilman and Traci Partin, is the Spanish language version of ENG-1054, Restoring Trees after a Hurricane. It is part of the Urban Forest Hurricane Recovery Program series. It provides a step-by-step guide for restoring trees after a hurricane or windstorm so that trees can bring beauty and shade back to the community with reduced risk. Published by UF Department of Environmental Horticulture, January 2007.